The Associations of Parenting Factors with Adolescent Body Mass Index in an Underserved Population - Elizabeth M. Schneider; Dawn K. Wilson; Heather Kitzman-Ulrich; Sara M. St. George; Kassandra A. Alia (Journal of Obesity)
Background. The current study examined parental factors related to risk of adolescent obesity within the context of a family systems framework. Methods. Seventy predominantly African American, low-income caregiver-adolescent dyads participated in the study. Validated measures of parental perceived child risk for development of type 2 diabetes mellitus, parental limit setting for sedentary behavior, and parental nurturance were evaluated as predictors of adolescent body mass index. Results. In this cross-sectional study, multiple linear regression demonstrated that parents of adolescents with higher zBMI reported worrying more about their child's risk of developing type 2 diabetes mellitus. Parent limit setting was also a significant predictor of adolescent zBMI. Contrary to expectations, higher levels of nurturance were associated with higher adolescent zBMI. Post hoc analyses revealed a trend towards a significant interaction between nurturance and limit setting, such that high levels of both parental nurturance and limit setting were associated with lower adolescent zBMI. Conclusions. Current findings suggest the importance of authoritative parenting and monitoring of adolescent health behaviors in the treatment of obesity.